Novel immunostimulatory effects of osteoclasts and macrophages on human γδ T cells - Pappalardo, Angela (Bone, 2015)
It has been widely reported that T cells are capable of influencing osteoclast formation and bone remodelling, yet relatively little is known of the reciprocal effects of osteoclasts for affecting T cell function and/or activity. In this study we investigated the effects of human osteoclasts on the function of γδ T cells, a subset of non-CD4(+) T cells implicated in a variety of inflammatory disease states. γδ T cells and CD4(+) T cells were isolated from peripheral blood of healthy volunteers and were co-cultured with autologous mature osteoclasts (generated by treatment with M-CSF and RANKL) before phenotypical and functional changes in the T cell populations were assessed. Macrophages, osteoclasts, and conditioned medium derived from macrophages or osteoclasts induced activation of γδ T cells, as determined by the expression of the early activation marker CD69. TNFα was a major mediator of this stimulatory effect on γδ T cells. Consistent with this stimulatory effect, osteoclasts augmented proliferation of IL-2-stimulated γδ T cells and also supported the survival of unstimulated γδ and CD4(+) T cells, although these effects required co-culture with osteoclasts. Co-culture with osteoclasts also increased the proportion of γδ T cells producing IFNγ, but did not modulate IFNγ or IL-17 production by CD4(+) T cells. We provide new insights into the in vitro interactions between human γδ T cells and osteoclasts/macrophages, and demonstrate that osteoclasts or their precursors are capable of influencing γδ T function both via the release of soluble factors and also through direct cell–cell interactions.